Management of Acceptance and Regard in Educational Relationships: A Study of Hamka's Perspectives in Tafsir Al-Azhar - Rangkuti, Bima Wahyudin; Shunhaji, Akhmad; Tahir , Muhammad Suaib (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
This research examines the management of acceptance and regard in educational relationships from Hamka's perspective in Tafsir Al-Azhar. Using the qualitative method of literature study, the main data source being Tafsir Al-Azhar itself as well as other sources to support it, three forms of management were found, namely non-dominative action. Non-dominative actions are actions, attitudes, or other things that do not give the impression of domination by parents or teachers over children or students. This non-dominative action is found in Hamka's interpretation of Q.S. Asy-Syu'arâ': 215. Another form of management is a serious response. This serious response concerns the way parents or teachers treat children or students. Responding to it with a serious response is not taking it lightly at all. This serious response can be found in Hamka's interpretation of Q.S. Yûsuf: 4-5. And reactive patience. Reactive patience is related to internal patience, which is externalized reactively to children or students in the form of reactions or responses that do not conflict with patience. This reactive patience is found in Hamka's interpretation of Q.S. Yûsuf: 16-18.